2020
DOI: 10.1590/0103-6440202003767
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dentistry YouTube Videos Related To COVID-19

Abstract: This study aimed to analyze the videos available on YouTube related to dentistry and the novel coronavirus (COVID-19), as there is no such analysis in the existing literature. The terms “dental” and “COVID-19” were searched on YouTube on May 9, 2020. The top 116 English-language videos with at least 300 views were analyzed by two observers. Data was saved for each video, including target audience, source, country of origin, content, number of views, time watched, average views, duration, like/dislike ratio, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 16 publications
4
43
0
3
Order By: Relevance
“…In some of the studies, in which health-related video analyses have been conducted, inconsistencies in viewer video interactions have been reported [30]. Similar to these results, although they were low-quality videos in terms of information content, the experience videos uploaded by patients were watched more often than the others' in the current study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In some of the studies, in which health-related video analyses have been conducted, inconsistencies in viewer video interactions have been reported [30]. Similar to these results, although they were low-quality videos in terms of information content, the experience videos uploaded by patients were watched more often than the others' in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…This discrepancy between viewing rate and information content could occurred because the patients' experience videos were more entertaining and immersive, and provided application-related experiences to others in a similar position [16][17][18]. Also, the fact that useful videos are ranked lower due to YouTube's ranking criteria could affect this result [17,30]. This indicated that an individual who researches BTX applications with the key words "masseter Botox" was more likely to encounter less useful videos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Two studies in Turkey investigated the quality of YouTube videos regarding COVID-19 information in dentistry. 49,50 One of these studies analysed the top 116 English videos with at least Review 300 views and showed moderate quality and useful information from these videos. 49 The other study, however, showed poor quality for 24 of 55 (43•6%) English videos, whereas good quality accounted for only 2 (3•6%) videos.…”
Section: Social Media As Disease Controlmentioning
confidence: 99%
“…Çalışmada incelenen videoların yalnızca bir gözlemci tarafından değerlendirilmiş olması da çalışmanın diğer bir sınırlılığı olarak görülebilir. Ayrıca, YouTube'a yüklenen videoların çoğunun İngilizce olduğu bilinmektedir, 24,34 ancak bu çalışmada yalnızca Türkçe videolar analiz edilmiştir. Analize farklı dillerin dahil edilmesi de çalışma sonuçlarını etkileyecektir.…”
Section: Discussionunclassified